The Implementation of Bilingual: A Study at SMPN 3 Jember as the Pilot Project of International Standard School - Ninuk Indrayani (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
This study aims to describe the phenomenon of bilingualism in the teaching and learning process at SMPN 3 Jember, particularly focusing on the implementation of code switching, code mixing, and style. The research design employed was qualitative descriptive, with data collection methods including interviews with bilingual class teachers, observations of teaching and learning activities in bilingual classes, and questionnaires distributed to students in bilingual classes. The findings concluded that the phenomena of code switching, code mixing, and style indeed occur, primarily initiated by the teachers. Bilingual teachers utilized code switching and code mixing when explaining or clarifying material by repeating the same content in two languages. Style also emerged in situations related to emotions. Penelitian ini bertujuan untuk mendeskripsikan fenomena bilingual dalam proses belajar mengajar di SMPN 3 Jember, terutama tentang pelaksanaan code switching, code mixing, dan style. Desain penelitian yang digunakan adalah deskriptif kualitatif dengan metode pengumpulan data menggunakan wawancara kepada guru pengajar kelas bilingual, observasi kegiatan proses belajar mengajar di kelas bilingual, dan angket kepada siswa yang berada di kelas bilingual. Kesimpulan dari hasil penelitian ditemukan bahwa fenomena code switching, code mixing, dan style memang terjadi, dan terutama dilakukan oleh guru. Guru kelas bilingual menggunakan code switching dan code mixing ketika ingin menjelaskan atau mengklarifikasi sesuatu, dengan cara mengulang materi yang sama dengan dua bahasa. Style juga terjadi dalam situasi-situasi yang berkaitan dengan emosi.